Conclusion. Le projet scientifique de la psychologie associationniste - Stéphane Madelrieux (Astérion)
This conclusion aims at giving an idea of the general project underlying the xixth century associationnist psychology beyond the diversity of authors and positions. We claim that the importance of the association of ideas was to allow psychology to be constituted as an empirical science of the mind. This project was made possible thanks to the new function attributed to the association from David Hume on, as it was considered not only as an habitual transition from one idea to another, but as the genetic principle of the whole mental life.